(untitled) (Baghdad Science Journal, 2025)
This study on the plant of Ain –AL Bason Catharanthus roseous showed the ability of callus cells that is produced by In Vitro culture technique and transformed to the accumulated media (MS 40gm/L sucrose ,2gm/L IAA Indole acetic acid , 0.5gm/L Tryptophan) to produce Vinblastine and Vincristine compounds. Extraction, purification and quantitive determination of Vinblastine and Vincristine compounds using High performance liquid chromatography technique (HPLC)were carried out. The results showed that the highest concentration of Vinblastine and Vincristine compounds were ( 4.653,12.5 (ppm /0.5 dry Wight respectively from transformed callus cells from MS 40 gm /L sucrose , 2 gm / L NAA Naphthaline acetic acid .